Analisis Jumlah Pengunjung dan Jumlah Wisata Terhadap PAD Kabupaten Lamongan - Haykal Abidin; Awawin Mustana Rohmah (Unisda Journal of Mathematics and Computer Science (UJMC), 2020)
Lamongan Regency is one of the regencies in East Java which is quite potential to support economic needs. One of the potentials in Lamongan is the entertainment and recreation sector, in this case tourism. Tourism is one of the sectors that has experienced an increase in investment so that it is able to increase economic activity and have an impact on Regional Original Income (PAD). To determine the effect of the amount of tourism on PAD in Lamongan Regency, multiple linear regression analysis and determination coefficient analysis were carried out. The results of this study indicate that the number of tourists greatly influences the PAD in Lamongan Regency and has increased.